The Impact of knowledge Workers in Organizational Excellence Field research in a number of the Iraqi industrial companies - علي شفاء محمد; هاشم ولدان عبد الستار (Journal of Economics and Administrative Sciences, 2018)
The Knowledge Workers is The Largest And Most Powerful Resource Of The Organizational Excellence it is A Precious Treasure, Therefore Find Organizations at present is looking for them and seek to invest their ideas For achieving excellence, creativity and access to the excellence Organizational , As a result of their importance in terms of engagement and influence in the success or failure of the as an organizational Of The Research is Measuring The Correlation And Impact Between Knowledge Workers And Organizational Excellence in Sample Of Companies Iraqi Industrial By Standing The Dimensions Of Knowledge Workers ( Characteristics , Skills , Roles , Competencies ) And The The Dimensions Of Organizational Excellence ( Strategic Planning ,Focusing on The Market And The Customer , The Formation And Analysis , The Effectiveness Of Operation , Business Results ) . The Purpose Of The Research is to identifying Knowledge and owned by these persons of capabilities make them distinct who are able to achieve excellence, Them And Protect Them This Included Community Study (5) Industrial Companies an Iraqi ( The General Company For Electrical Industries, The General Company For Leather Industries, The General Company for Vegetable Oils Industries, The General Company for Cotton Industries, The Company Electronic Industries). To Achieve The Aim Of The Research , The Researcher Designed A Questionnaire To Gather Preliminary Information, Consisting Of (65) Items And Distribute Them To Members Of The Research Sample And The (The Department Heads, General Directors, Directors Of The Unit Or Division) Was Conducted Interviews With Knowledge Workers Where The Members Of The Sample Respondents (111) Out Of (125) in The Light Of That Has Been Collecting And Analysis Data And Test Hypotheses , The Results Showed That There is A Correlation And High Impact Among The Knowledge Workers And Organizational Excellence Any Greater The Knowledge Workers in Companies increased Their Ability To Achieve Organizational Excellence as Recommended By Research That Organizational Excellence Comes from ideas presented by of knowledge Workers Understanding the main element for the success of the business that provided by Organizational Excellence